2022
DOI: 10.7150/thno.72511
|View full text |Cite
|
Sign up to set email alerts
|

Continuous centrifugal microfluidics (CCM) isolates heterogeneous circulating tumor cells via full automation

Abstract: Understanding cancer heterogeneity is essential to finding diverse genetic mutations in metastatic cancers. Thus, it is critical to isolate all types of CTCs to identify accurate cancer information from patients. Moreover, full automation robustly capturing the full spectrum of CTCs is an urgent need for CTC diagnosis to be routine clinical practice. Methods: Here we report the full capture of heterogeneous CTC populations using fully automated, negative depletion-based continuous centrifugal microfluidics (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…2020-10-033). CTCs and circulating fetal cells were isolated in a similar manner to the previous method …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020-10-033). CTCs and circulating fetal cells were isolated in a similar manner to the previous method …”
Section: Methodsmentioning
confidence: 99%
“…CTCs and circulating fetal cells were isolated in a similar manner to the previous method. 20 Fabrication of HypICC Platform. Owing to its biocompatibility and high optical transmittance, polydimethylsiloxane (PDMS) is suitable for visually monitoring biological cells.…”
Section: Methodsmentioning
confidence: 99%
“…The recovery rate is more than 90% and the depletion rate is 99.9%. 39 In addition, the detection and analysis of blood samples from 30 patients with non-small cell lung cancer showed that there was a good correlation between the EGFR mutation spectrum of CTCs and the spectrum of circulating tumor DNA (CtDNA). In patients with insufficient ctDNA for mutation analysis, CTC analysis may be an auxiliary decision-making tool.…”
Section: Technologies For Ctc Enrichment In Vitromentioning
confidence: 99%
“…In this study, we introduce a fully automated continuous centrifugal microfluidics-based NK disc (CCM-NKD) for NK cell isolation. The centrifugal microfluidic system has been investigated and applied in various fields, including the isolation of rare cells such as CTCs , and trophoblasts, as well as primary neuron cell isolation and nucleic acid testing . The CCM-NKD implements a negative selection strategy, eliminating non-NK cells to increase the NK cell concentration.…”
Section: Introductionmentioning
confidence: 99%